2019
DOI: 10.1103/physrevx.9.011012
|View full text |Cite
|
Sign up to set email alerts
|

Higher-Order Bulk-Boundary Correspondence for Topological Crystalline Phases

Abstract: We study the bulk-boundary correspondence for topological crystalline phases, where the crystalline symmetry is an order-two (anti)symmetry, unitary or antiunitary. We obtain a formulation of the bulk-boundary correspondence in terms of a subgroup sequence of the bulk classifying groups, which uniquely determines the topological classification of the boundary states. This formulation naturally includes higher-order topological phases as well as topologically nontrivial bulk systems without topologically protec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
271
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 300 publications
(279 citation statements)
references
References 77 publications
5
271
0
Order By: Relevance
“…To the best of our knowledge, in the previous studies, explanations of bulk-hinge correspondence are roughly classified into two: (i) k · p theory approach [22][23][24][31][32][33]35,37,40,41 , and (ii) Wannier approach 24,25,36,40 . In (i), one starts from the surface Dirac Hamiltonian, which represents anomalous gapless surface states as a low-energy effective Hamiltonian for the surface.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, in the previous studies, explanations of bulk-hinge correspondence are roughly classified into two: (i) k · p theory approach [22][23][24][31][32][33]35,37,40,41 , and (ii) Wannier approach 24,25,36,40 . In (i), one starts from the surface Dirac Hamiltonian, which represents anomalous gapless surface states as a low-energy effective Hamiltonian for the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, it was recently demonstrated that a crystal with a crystalline-symmetry compatible bulk topology may manifest itself through protected boundary modes of codimension greater than one [14][15][16][17][18][19][20][21][22][23]. Such insulating and superconducting phases are called higher-order topological insulators and superconductors (HOTI/SCs).…”
mentioning
confidence: 99%
“…The trivial phase has p = (0, 0), the dipolar phase has p = (1/2, 0) or p = (0, 1/2) and the quadrupolar phase has p = (1/2, 1/2). As the polarisation is calculated from the Wannier bands related to the bulk spectrum, the appearance of zero modes in the corner is related to a gap closing in the bulk, showing a new kind of bulk-boundary correspondence [16]. (1) showing the topological phases.…”
Section: Quadrupolar Topological Insulatormentioning
confidence: 98%